Regression methods for evaluation of the underwater noise levels in the Slovenian Sea - Popit, Andreja (RMZ-materials and geoenvironment, 2021)
Anthropogenic underwater noise pollution of seas and oceans caused by shipping can have negative effects on marine animals. The aim of this study was to eval-uate quantitatively how much the underwater noise levels in the Slovenian Sea were influenced by anthro-pogenic pressures and meteorological parameters in the period from 2015 until 2018. For this purpose, correlation method and least squares multiple linear regression analysis were used. The results of this study show that the correlation of underwater noise levels with the dredging activity is significant but low, while correlation with the ship densities is insignifi-cant, which could be due to reduced sound wave prop-agation in the shallow sea levels. Correlation of the underwater noise levels with the wind speed was sig-nificant but low to medium, which could be explained by the breaking waves generated by the wind that produced sound.
Keywords: anthropogenic pressures; antropogeni pritiski; correlation; korelacija; meteorological parameters; multipla linearna regresija; multiple linear regression; ogrožanje in varstvo hidrosfere; podvodni hrup; underwater noise; vodno okolje